2018
DOI: 10.1111/emre.12323
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Juxtapose of the Effects of Self‐image on Entrepreneurial Career along the Spectrum of Nascent to Actual Entrepreneurs

Abstract: This empirical study extends beyond efforts to contrast entrepreneurs with non‐entrepreneurs and elucidates comparisons among entrepreneurs. Specifically, it investigates capability and vulnerability self‐images among three groups of entrepreneurs to understand differences in perceptions. Using a sample of 725 graduate young entrepreneurs, multinomial logistic regression shows that low‐intention nascent, high‐intention nascent and actual entrepreneurs perceive their potential and fears differently. The evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
(167 reference statements)
0
9
0
Order By: Relevance
“…This research advances image theory (Beach, 1990) in entrepreneurship (e.g. Salavou and Lioukas, 2019;Tang, 2016) by using its concept of shocks and violations to the self-image to understand how cross-cultural experience can function as a constructive category of turbulence with regard to developing entrepreneurial sensing aptitudes. Leading scholars in entrepreneurship have noted the importance of the self-image for the opportunity recognition process, mainly in terms of its content (e.g.…”
Section: Contributions and Implications For Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…This research advances image theory (Beach, 1990) in entrepreneurship (e.g. Salavou and Lioukas, 2019;Tang, 2016) by using its concept of shocks and violations to the self-image to understand how cross-cultural experience can function as a constructive category of turbulence with regard to developing entrepreneurial sensing aptitudes. Leading scholars in entrepreneurship have noted the importance of the self-image for the opportunity recognition process, mainly in terms of its content (e.g.…”
Section: Contributions and Implications For Researchmentioning
confidence: 91%
“…Collectively, image theory has been helpful for understanding how managers and entrepreneurs "connect the dots" of their experiences in line with their status-quo perceptions (e.g. Mitchell and Shepherd, 2010;Penney et al, 2019;Salavou and Lioukas, 2019;Tang, 2016). More specifically, image theory posits that as individuals are constantly flooded with information in their daily experiences, their images function as screening devices (Beach and Mitchell, 1998).…”
Section: Image Theory and Regulatory Orientationsmentioning
confidence: 99%
“…The related concept of entrepreneurial orientation is also positively impacted by narcissism, as numerous studies have found (Paulhus and Williams, 2002; Davila et al , 2003). This dimension includes the entrepreneur’s self-image, which can influence entrepreneurial aspirations (Salavou and Lioukas, 2019). As having a positive self-attitude is helpful in entrepreneurial work, it is also heavily correlated with narcissistic tendencies, for example, the need for power or admiration (Campbell et al , 2011).…”
Section: The Entrepreneurial Journey and The Role Of Narcissismmentioning
confidence: 99%
“…In general, considering nascent entrepreneurs are more flexible than experienced ones, they are more likely to find new opportunities and have better learning ability and adaptability (Cunningham and Anderson, 2018). Thus, when the entrepreneurial entry speed is faster and managerial seniority is low, the host has a more urgent attitude to accumulate new knowledge and resources quickly, as well as the positive attitude to spot opportunities in the market, learn and adapt to change (Salavou and Lioukas, 2019). At this point, host popularity has the strongest positive impact on host expansion.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%